The relationship between consumer loyalty and time of innovation through coffee shop product innovation variables - Wachdijono Wachdijono; Berlyana Febriyanti; Sandi Nasrudin Wibowo; Ika Tri Wahyuni (RTTM, 2023)
Innovation product result from various types of processes that combine each other influence, one of which other aims to increase decision consumer purchases. Through product innovation, it is hoped that consumers will continue to buy and be loyal, especially in the era of business competition. Therefore, research on product innovation becomes essential, specifically on efforts that currently stand up in whole corner soil water, that is, effort coffee shop. The study aims to know the variables influencing coffee shop product innovation in Cirebon City, Indonesia. The research method with the survey and the research population is coffee shop consumers. Technique the determination of the sample size based on the loading factor number of 0.65 so that the number of samples set as big as 70 respondents. Technique analysis data use the instrument Structural Equation Model (SEM) with the application AMOS. The results study conclude that variable timing innovation directly affects the innovation product coffee shop, whereas variable competence managerial competence, human resource competence, ownership of R & D facilities, and system networks information do not affect the innovation of coffee shop products in Cirebon City. Research result This is useful for coffee shop business actors to develop product innovations to win competition efforts by healthy